Letter from the Editors - Joe Pellegrino; Delores Liston; Delena Gatch (International Journal for the Scholarship of Teaching and Learning)
This letter introducing the second issue in volume 18 presents a personal reflection from one member of the editorial team on the contributions of the other two editors.